Big Nate : Blow the roof off! - Peirce, Lincoln; Peirce, Lincoln (Kansas City, Missouri : Andrews McMeel Publishing, 2020)
A reprinting of the "Big Nate" comic strip, that follows the adventures of eleven-year-old Nate Wright, who's band is invited to play at the P.S. 38 annual open house.
These strips appeared in newspapers from September 14, 2015, through February 28,2016.
2.8.
3-6.
GN310L
Keywords: Big Nate -- Comic books, strips, etc. -- Juvenile fiction; Middle school students -- Comic books, strips, etc -- Juvenile fiction; Middle schools -- Comic books, strips, etc -- Juvenile fiction; Human behavior -- Comic books, strips, etc -- Juvenile fiction; Schools -- Comic books, strips, etc -- Juvenile fiction; Big Nate -- Fiction; Middle school students -- Fiction; Middle schools -- Fiction; Behavior -- Fiction; Schools -- Fiction; Humorous comics; Comics (Graphic works)